Meningkatkan Kemampuan Literasi dan Kepercayaan Diri Peserta Didik dengan Metode Groupwork - Melicha Athalia Pelawi; Gusti Pirandy (Yayasan Literasi Sains Indonesia, 2023)
Literacy education in Indonesia currently needs to be improved. Seeing that since the pandemic occurred, Indonesia's literacy rate has decreased. Because the teaching and learning process is passed online, the government makes innovations, one of which is the teaching campus. In the process of this activity, the author is required to be an agent of change. To improve proving students' literacy and confidence as clients, the authors create programs that support increased literacy and confidence. This program is carried out at UPT SDN 060813, Jl.Halat No.48, Medan Kota. With a total of 14 students in grade, V. this program lasts for approximately 3 months. The method implemented in this program is group work with several stages, namely: (1) Engagement, (2) Intake and Contract, (3) Assessment, (4) Planning, (5) Intervention, (6) Evaluation, and (7) Termination. The results of this program show an increase in students' literacy and confidence as clients. At the initial meeting, there were still students who lacked literacy, and in terms of confidence, they read in low voices and intonation that was not clear. But as the program progressed, the authors noticed changes taking place in students' literacy and confidence.